Marissa J. Moorman, Powerful Frequencies. Radio, State Power and the Cold War in Angola, 1931–2002 (Ohio: Ohio University Press, 2019), 240pp, paperback, ISBN 9780821423707 - Gunner, Liz (Kronos: Southern African Histories, 2019)
This important book is a substantial addition to the growing studies of the importance of radio on the African continent. It crosses bridges between the language divides in Africa set up by colonial rule, thus playing a key role in the current moves away from the fragmented regional approaches of earlier African studies. Another important factor is the ease with which the author weaves in the strands of global politics with the intensely local. Radio has always enabled this double view, as studies of radio and empire by Simon Potter, Peter Bloom and others have shown. Here we see its operations again, through the detailed and often startling material that the author brings to light, as she draws on and synthesises a range of archives, both sonic and written...